Dissecting the Tahāfut Al-Falāsifah as the Critism of Ghazali Against the Muslim’s Philosopy - Qurrotul Aini (Farabi, 2016)
This research is the study of library research which raised the criticism of al-Ghazālī against the muslim philosophers in Tahāfut al-Falāsifah. And in this paper there are two questions; first, what is the purpose of al-Ghazālī in writing the Tahāfut al-Falāsifah? Second, Is it true that this work is representation of the conflict between philosophy and dogma; between revelation and the ratio; or between orthodoxy and heterodoxy. By using historical and content analysis to elucidate the criticism of al-Ghazālī against the muslim philosophers in Tahāfut al-Falāsifah. Then, the results of this research are, first al-Ghazālī wrote the Tahafut to do contestation against epistemology philosophical superiority claims, which was directed to their conclusions, instead of questioning the validity of logic as philosophical reasoning methodology. Second, the critism of al-Ghazālī cannot be seen as a reaction of orthodoxy or dogma against the philosophy. He should be viewed as a muslim scholar who has an important role in the naturalization of greek philosophical tradition and its adaptation to the building of islamic thought.